A modular and low-cost data acquisition card design with multitasking support - ERDAL, HASAN; SAVAŞ, KENAN (ELSEVIER SCIENCE BV, 2010)
This paper describes a microcontroller-based, low-cost and multi-function data acquisition card design. A wide user audience for this product and a wide field of use are considered on the basis of containing many functions. Many kinds of projects in universities need data collection interfaces, which greatly increases the cost of project. Comparing with other data acquisition cards, this design comes to the flexibility to change the number of and the functions of ports which is the part of the designed data acquisition card. Also with this design more than one system can be controlled simultaneously. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Data acquisition card design; PIC based data acquisition; low-cost data acquisition; modular data acquisition